2015
DOI: 10.1038/srep18161
|View full text |Cite
|
Sign up to set email alerts
|

Collembola at three alpine subarctic sites resistant to twenty years of experimental warming

Abstract: This study examined the effects of micro-scale, site and 19 and 21 years of experimental warming on Collembola in three contrasting alpine subarctic plant communities (poor heath, rich meadow, wet meadow). Unexpectedly, experimental long-term warming had no significant effect on species richness, effective number of species, total abundance or abundance of any Collembola species. There were micro-scale effects on species richness, total abundance, and abundance of 10 of 35 species identified. Site had signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…A similar plot-scale effect was found previously in a study on Collembola at the same sites32. Small-scale heterogeneity could thus have an important buffering effect on soil fauna32, in a similar way as boulders in high alpine areas can buffer species from extreme heat events50. Studies on mountain-top boulder fields have shown that they can provide microhabitat temperature buffering for extreme events (heat waves) over short distances, and that they have probably functioned as important refugia during historical climate fluctuations50.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A similar plot-scale effect was found previously in a study on Collembola at the same sites32. Small-scale heterogeneity could thus have an important buffering effect on soil fauna32, in a similar way as boulders in high alpine areas can buffer species from extreme heat events50. Studies on mountain-top boulder fields have shown that they can provide microhabitat temperature buffering for extreme events (heat waves) over short distances, and that they have probably functioned as important refugia during historical climate fluctuations50.…”
Section: Discussionsupporting
confidence: 88%
“…In general, unless associated with decreased soil moisture, increased warming in the polar regions is predicted to increase soil invertebrate numbers due to microbial communities and plant communities increasing in productivity and complexity27. However, a recent long-term study found no impact of experimental warming on Collembola at sub-arctic/alpine sites32. In the present study, we examined the impact of 19 and 21 years of experimental warming, field site and plot scale on soil parameters (soil carbon (C), nitrogen (N), C/N ratio, moisture and pH in the organic and mineral soil layers), total mite density, juvenile and adult stages of mites, density of major mite groups and the most common species of oribatid mites in three contrasting alpine/subarctic plant communities.…”
mentioning
confidence: 99%
“…Other organism groups may remain resistant or may be similarly affected, which would be of particular concern owing to the above-average level of endemic invertebrates compared to elevations below the timberline in the Alps (Rabitsch et al 2016). For alpine soil arthropod abundance, experimental warming was most effective when combined with nutrient addition (Hågvar and Klanderud 2009), whereas a long-term warming experiment had no effect on richness and abundance of springtails in alpine subarctic ecosystems (Alatalo, Jägerbrand, and Čuchta 2015). Changes in occurrence and activities of microorganisms would be especially relevant to climate change considering their attributes as key players for methane formation and consumption, belonging to methanogenic archaea and methanotrophic bacteria, respectively (Crutzen and Lelieveld 2001;Hofmann et al 2016b;Praeg, Wagner, and Illmer 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Likely, the intensity of the warming applied was moderate not only for collembolans (although see Petersen, 2011, for a further discussion on the modest warming effects found in some of the sites) but also for plant communities and ecosystem functions like net primary productivity and respiration, which were also rather insensitive to the warming treatment (Kröel-Dulay et al, 2015;Reinsch et al, 2017). Recent findings have nonetheless revealed that springtails, and in general soil fauna, may be quite resistant to increases in temperature (Alatalo et al, 2015;Holmstrup et al, 2017Holmstrup et al, , 2018. Recent findings have nonetheless revealed that springtails, and in general soil fauna, may be quite resistant to increases in temperature (Alatalo et al, 2015;Holmstrup et al, 2017Holmstrup et al, , 2018.…”
Section: Discussionmentioning
confidence: 98%